Determinan Penghambat Menabung Pada Bank Syariah: (Studi Kasus Pegawai Og Hospital Binjai) - Fitria Hanum; Fauzi Arif Lubis; Wahyu Syarvina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to find out (1) whether knowledge is an obstacle for OG hospital employees to save in sharia banks (2) whether location is an obstacle for OG hospital employees to save in sharia banks (3) whether the work environment is an obstacle for OG hospital employees to save in banks sharia (4) whether knowledge, location and work environment are obstacles for OG hospital employees to save in sharia banks. This type of research is quantitative. The population and sample in this study were 32 Muslim employees at OG Hospital. The data collection technique uses a questionnaire. The analysis technique used is multiple linear regression with the help of SPSS software. The research results show that first, the knowledge variable partially inhibits OG hospital employees from saving in Islamic banks with a calculated t value of 2.244 > 2.048 and a significance value of 0.033 < 0.05. Second, the location variable is not partially an obstacle for OG hospital employees to save at Islamic banks with a calculated t value of 0.675 < 2.048 and a significance value of 0.505 > 0.05. Third, the work environment variable partially inhibits OG hospital employees from saving at Islamic banks with a calculated t value of 3.137 > 2.048 and a significance value of 0.004 < 0.05. Fourth, the variables of knowledge, location and work environment simultaneously become obstacles for OG hospital employees to save at Islamic banks with a calculated F value of 28.062 > F table 2.95 with a significance value of 0.000 < 0.05.